Quality Education and the Use of English Language as a Medium of Instruction in Rwandan Schools: An Interpretivist Study - Jean de Dieu Karasenga; Jean Baptiste Nzanana (International Journal of Educational Review, 2022)
The purpose of the study upon which this paper is based was to investigate the level at which school leaders and teachers use English as a medium of instruction to promote quality education in their schools. Data were collected using questionnaires, interviews, and classroom observations at a Twelve-Year Basic Education school located in Muhanga District in the Southern Province of Rwanda. Participants consisted of two school leaders and 18 teachers from the school. Results suggest that teachers use the English language at minimal level during classroom activities. Pedagogical implications regarding what could be done to effectively use the English language in classrooms in order to foster quality education will be discussed.